Microfabrication methods - Živkov, Andreja (Journal on Processing and Energy in Agriculture, 2026)
This paper contains an overview of fabrication methods used for construction for different microfluidic devices and some example applications. All the different procedures, methods and their respective variants are collectively called microfabrication methods. Microfabrication as a field holds great value in microfluidics as the fabrication method closely determines the possible application of the device. The overview of fabrication methods can be given regarding the mechanical properties of the materials used. In this case the observed mechanical property is the rigidity of the material, and they are classified as hard, plastic and soft materials. Other material mechanical properties affect the possibility of use in hot or cold, reactive or neutral environments and one of the most important characteristics of microfluidic devices biocompatibility. Some of the most widespread methods shown in the paper are photolithography and its variants, etching methods used for silicone and glass, PDMS molding, micro milling and 3D printing. As well as paper microfluidics as a great representation of biocompatible microfluidic devices used in medical applications.
Keywords: Keywords: microfabrication, photolithography, etching, micromilling, 3D printing, paper microfluidics, PDMS; PMMA; COC